Reduction of ammonia loss through mixing urea with zeolite, peat soil water, and sago waste water - Omar, Latifah (2011)
Ammonia volatilization is one of the major mechanisms which lead to poor urea-N use efficiency. Two laboratory incubation experiments were conducted to study the effects of mixing urea with zeolite, peat soil water, and sago waste water on NH3 volatilization, soil exchangeable NH4 +, available NO3 - contents compared with urea without additives under waterlogged and non-waterlogged conditions. The study compared seven different treatments which were: soil alone (T0), urea without additives (T1), urea mixed with 175 mL peat soil water and 0.75 g zeolite (T2), urea mixed with 175 mL peat soil water and 1.0 g zeolite (T3), urea mixed with 175 mL peat soil water (T4), urea mixed with 175 mL sago waste water and 0.75 g zeolite (T5), urea mixed with 175 mL sago waste water and 1.0 g zeolite (T6), and urea mixed with 175 mL sago waste water (T7). The mixtures (T2, T3, T4, T5, T6 and T7) significantly reduced NH3 volatilization and also improved retention of soil exchangeable NH4 + compared with urea without additives (T1). All the mixtures of zeolite, sago waste water, and peat soil water with urea significantly increased soil exchangeable NH4 +, available NO3 - contents. The mixtures of sago waste water, zeolite, and peat soil water with urea delayed urea hydrolysis and NH4 + accumulation under waterlogged condition than under nonwaterlogged condition. These mixtures were further tested (scale up) in a pot experiment (greenhouse) whereby maize (Zea mays L.) hybrid No. 5 was used as a test crop. The objectives of this greenhouse study were to evaluate the effects of the treatments on: (1) Nitrogen, P, and K uptake and their use efficiency in maize cultivation, and (2) Soil exchangeable NH4 +, available NO3 -, pH, exchangeable K, and available P contents. The treatments evaluated were: No fertilizer (T0), 2.02 g urea (T1), 2.02 g urea + 30 g zeolite + 7 L peat soil water (T2), 2.02 g urea + 40 g zeolite + 7 L peat soil water (T3), 2.02 g urea + 30 g zeolite + 7 L sago waste water (T4), 2.02 g urea + 40 g zeolite + 7 L sago waste water (T5), 2.02 g urea + 7 L peat soil water (T6) and 2.02 g urea + 7 L sago waste water (T7). Triple Super Phosphate (TSP) and Muriate of Potash (MOP) were used as sources of P and K for all the treatments except for T0. These fertilizers were applied twice that is 10 and 28 days after planting. Phosphorus and K requirements of the test crop were supplemented by applying TSP and MOP (standard rate for the test crop) to plants of all the treatments except T0. The mixtures of sago waste water, zeolite, and peat soil water with urea significantly improved maize dry matter, N, P, K uptake and N, P, K use efficiency compared with urea without additives. These mixtures also significantly increased soil exchangeable NH4 +, K, Ca, Mg, available P, and NO3 - contents compared with urea without additives. Amending urea with sago waste water and peat soil water can reduce NH3 loss by encouraging formation of NH4 + and NO3 - over NH3. Additionally, the mixtures ensure N, P, K uptake and their use efficiency while at the same time making soil NH4+, K, Ca, Mg, P, and NO3- available for plant use.